IS THERE A LINK BETWEEN VITAMIN D DEFICIENCY AND INSULIN RESISTANCE AMONG NEWLY DIAGNOSED TYPE 2 DIABETES PATIENTS? A STUDY DONE IN SUDAN - Mohamed Abdelrahim Ahmed, Ogail Yousif Dawod, Amar Babikir Elhussein, Abdulrahman A. Alsayegh, Husham E. Homeida, Hind Ali Osman; Solima I. Yagoob, Nagwa E.E. Malik, Monami Mukherjee Mondal, Ibrahim Ismail Mohammed Abu, Asaad Khalid, Nahid Mahmoud Hassan Elamin (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
BACKGROUNDS AND AIMS: Diabetes mellitus remains one of the most challenging diseases, with increasing morbidity and mortality, despite excessive research. The objective of this study is to establish the association between vitamin D concentrations and insulin resistance in individuals recently diagnosed with diabetes (type 2). METHODS: In this descriptive study (cross-sectional study), 65 randomly chosen non-diabetic controls and 115 recently diagnosed diabetic participants were enrolled. During the referral for diabetes mellitus diagnosis, fasting blood samples were collected from both patients and control subjects. Plasma was used to measure the concentrations of vitamin D, as well as the levels of insulin and plasma glucose during fasting. The homeostasis model assessment-estimated insulin resistance (HOMA-IR) was calculated using fasting insulin and glucose to assess insulin resistance. Each participant’s weight, length, and age were recorded; these measurements were used to group the participants according to age and body mass index (BMI). Hierarchical regression analysis was performed to determine the impact of gender, age, BMI, and vitamin D on fasting insulin level and insulin resistance. RESULTS: The mean vitamin D concentration was significantly lower in newly diagnosed diabetics compared to controls (P ˂ 0.001). In the study group, Vitamin D levels averaged 10.7 ng/ml with a standard deviation of 7.9, while the control group had an average of 56.5 ng/ml with a standard deviation of 29.0. In contrast, the study group exhibited a significantly higher mean plasma insulin level compared to the control group (P < 0.001). Insulin level was (19.7 ± 6.2 m U/L) and (9.5 ± 2.4 m U/L) among diabetic and control groups respectively. Hierarchical regression analysis confirmed a significant negative correlation between the amount of vitamin D and insulin during fasting and insulin resistance (P= 0.0001). CONCLUSION: Vitamin D deficiency is strongly related to hyperglycemia, hyperinsulinemia, and insulin resistance in newly diagnosed diabetic patients (type 2).